2003
DOI: 10.1063/1.1615701
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Schottky contacts on n-type 4H–SiC using IrO2 and RuO2

Abstract: Thermally stable Schottky contacts on n-type 4H-SiC with high Schottky barrier height were demonstrated by annealing the rare earth metal contacts ͑Ir and Ru͒ under O 2 ambient. The formation of rare earth metal oxides (IrO 2 and RuO 2 ) after O 2 annealing led to the increase of Schottky barrier height ͑Ͼ1.9 eV͒ and a low reverse leakage current (ϳ10 Ϫ9 A/cm 2 ). Synchrotron radiation photoemission spectroscopy showed that the work function of IrO 2 is higher about 0.23 eV than that of Ir and the binding ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Because decreases in basal levels of adenylyl cyclase activity are difficult to detect, we treated the cells concurrently with isoproterenol, which stimulates adenylyl cyclase through endogenous ␤-adrenergic receptors coupled to G␣ s . Consistent with previous studies (18,38), expression of WT RGS16 or WT RGS4 inhibited the negative regulation of adenylyl cyclase activity induced by somatostatin compared with vector-transfected cells (Fig. 2).…”
Section: A Cysteine Residue In the Rgs Box Is Critical For Rgs16supporting
confidence: 79%
“…Because decreases in basal levels of adenylyl cyclase activity are difficult to detect, we treated the cells concurrently with isoproterenol, which stimulates adenylyl cyclase through endogenous ␤-adrenergic receptors coupled to G␣ s . Consistent with previous studies (18,38), expression of WT RGS16 or WT RGS4 inhibited the negative regulation of adenylyl cyclase activity induced by somatostatin compared with vector-transfected cells (Fig. 2).…”
Section: A Cysteine Residue In the Rgs Box Is Critical For Rgs16supporting
confidence: 79%
“…However, the mechanism by which RGS proteins recognize GPCRs to confer signaling specificity remains largely unknown. In vitro studies have found that RGS2 shows preference for G q class G ␣ subunits (35), whereas RGS4 attenuates both G i -and G q -mediated signaling (36)(37)(38). Biochemical evidence suggests that the divergent N-terminal domain of RGS proteins participates in GPCR recognition (39), and signaling specificity in vivo is conferred by interaction of RGS proteins with receptor complexes (40).…”
Section: Discussionmentioning
confidence: 99%
“…It was also noticeable that, without PTX treatment, cells expressing the G␣ o RGS/PTXi mutant were more efficiently inhibited by morphine and DAMGO than cells expressing only G␣ o PTXi. In a series of experiments using the opposite approach, expression of RGS4 or G␣-interacting protein in HEK293 cells reduced the level of somatostatin receptor-induced inhibition of cAMP accumulation (31), demonstrating the ability of RGS proteins to control the magnitude of inhibitory G protein signaling. Our data extend this by demonstrating a role for endogenous RGS proteins in this effect.…”
Section: Discussionmentioning
confidence: 99%